Enviromental impact study for the installation and operation of Papelera Gotelli - Salas, Norma (2010)
The Study of Impact Ambient (EIA) has by purpose of evaluating the existing environmental conditions, with the purpose of taking measures to reduce and/or eliminating the potential impacts to generate in the stages of construction and operation of the plant of Wastebasket Gotelli SAC, the one that will be dedicated to the manufacture of hygienic paper. In the matrix of identification and evaluation of environmental impacts one determined more significant the environmental impacts that the execution of the project and the causes of such will be generated due to. In the Plan of Environmental Handling the measures of mitigacion for the identified foreseeable impacts according to the characteristics of the project and to the environmental components of the influence area have settled down. Here it will be developed the programs of prevention, monitoreos, and contingencies, handling of solid remainders, plan of contingency and closing of corresponding operations.